Implikasi Kuliah Kerja Nyata Dalam Pengembangan Keagamaan Bagi Remaja di Desa Ulumahuam - Windi Mariska Suryani Siregar; Yani Lubis (Transformasi Manageria: Journal of Islamic Education Management, 2023)
The purpose of this study is to determine the role of parents' companions in supervising their children's use of gadgets in early childhood in Ulumahum Village, which is located in Silangkitang sub-district, South Labuhan Batu Regency. The literature review method was used to write this article (Literatur Research). At the moment, one of the goals of KKN is to promote religious knowledge and assist the government in hastening the development of religion and education. The goal is to improve the quality of religion and education in the community through training, counseling, and other means. The primary focus of this study in religious development and development is youth. Because basically adolescence is a progressive period. Keywords: Youth, Religious Development and Implications